Hydroxyl‐Functionalized Imidazoles: Highly Active Additives for the Potassium Iodide‐Catalyzed Synthesis of 1, 3‐Dioxolan‐2‐one Derivatives from Epoxides and Carbon Dioxide. Issue 12 (10th October 2014) - Werner, Thomas; Tenhumberg, Nils; Büttner, Hendrik
Abstract 4(5)‐(Hydroxymethyl)imidazole and potassium iodide were identified as an efficient catalyst system for the cycloaddition of epoxides and carbon dioxide producing 1, 3‐dioxolan‐2‐one derivatives under solvent‐free conditions. The high activity of the catalyst system even at 60 °C was probably due to synergistic effects between potassium iodide and the substituted imidazole. Various functionalized and nonfunctionalized terminal epoxides as well as internal epoxides were converted into the corresponding cyclic carbonates in high yields (up to 99 %) under mild reaction conditions within a short reaction time. Compared with the previously reported amino alcohols e.g. triethanolamine based catalyzed synthesis of cyclic carbonates, the catalyst system described herein demonstrates a higher activity toward a broad substrate scope